Metaheuristic optimization in power engineering - Radosavljević, Jordan (IET energy engineering series, 2018)
This book describes the principles of solving various problems in power engineering via the application of selected metaheuristic optimization methods including genetic algorithms, particle swarm optimization, and the gravitational search algorithm.